2020
DOI: 10.1002/chem.202000294
|View full text |Cite
|
Sign up to set email alerts
|

Two‐Dimensional MOF and COF Nanosheets: Synthesis and Applications in Electrochemistry

Abstract: Metal–organic framework (MOF) and covalent organic framework (COF) nanosheets are a new type of two‐dimensional (2D) materials with unique design principles and various synthesis methods. They are considered ideal electrochemical devices due to the ultrathin thickness, easily tunable molecular structure, large porosity and other unique properties. There are two common methods to synthesize 2D MOF/COF nanosheets: bottom‐up and top‐down. The top‐down strategy mainly includes ultrasonic assisted exfoliation, elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
95
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 196 publications
(102 citation statements)
references
References 148 publications
0
95
0
Order By: Relevance
“…In order to solve the problems of low yield and aggregation in the preparation of MOF and COF nanosheets by sonication and mechanical exfoliation, chemical exfoliation has been developed to regulate the interlayer interactions through controllable chemical reactions of interlayer organic molecules, thus decreasing damage of the in-plane structure in MOF and COF nanosheets [28].…”
Section: Chemical Exfoliationmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to solve the problems of low yield and aggregation in the preparation of MOF and COF nanosheets by sonication and mechanical exfoliation, chemical exfoliation has been developed to regulate the interlayer interactions through controllable chemical reactions of interlayer organic molecules, thus decreasing damage of the in-plane structure in MOF and COF nanosheets [28].…”
Section: Chemical Exfoliationmentioning
confidence: 99%
“…2). However, compared with bulk MOFs and COFs, MOF and COF nanosheets own more desirable properties such as ultrathin thickness, large lateral size, more active sites on the surface, and more flexibility, which are considered as good candidates for potential applications that cannot be achieved by bulk materials, and are also promising for the performance improvement in various applications [28][29][30]. Although MOF and COF nanosheets share many similar characteristics of porous materials nanosheets, they still keep their own unique advantages, thus leading to the different performances in various applications, probably owing to their different compositions and coordination modes.…”
Section: Introductionmentioning
confidence: 99%
“…37 The crystalline PGF-1 product shows remarkable Li + ion-storage capability up to 842 mAh g -1 when used as an electrode material in a Li-ion battery system, and can be fast charged at 6 C. Impressively, they demonstrated that the ordered self-assembling product has great advantages in capacity and rate-capability over applications, based on their ordered self-assembled structure. [38][39][40][41] The well- the electrolyte. In many materials, the SEI has to cope with large mechanical stresses without cracking or the loss of connection due to volume changes.…”
Section: Nanoscale Porous Materialsmentioning
confidence: 99%
“…Covalent organic frameworks (COFs) are a class of crystalline porous polymers with an atomically precise integration of building blocks into two-or three-dimensional topologies which were characterized by light weight elements and strong covalent bonds. [28][29][30][31][32] In 2005, Yaghi and co-workers, for the first time, synthesized two pure two-dimensional (2D) organic frameworks, named COF-1 and COF-5. [33] Subsequently, a great variety of COFs with various structures have emerged and their applications in energy storage, [34][35][36][37] drug delivery, [38] adsorption, [39] separation, [40] catalysis, [41,42] optoelectronics [43,44] and sensing [45] have been widely investigated.…”
Section: Introductionmentioning
confidence: 99%
“…In comparison with conventional polymers, porous organic frameworks show outstanding advantages because their robust networks can enhance the stability and provide open pores that facilitate the infiltration of electrolyte ions. Covalent organic frameworks (COFs) are a class of crystalline porous polymers with an atomically precise integration of building blocks into two‐ or three‐dimensional topologies which were characterized by light weight elements and strong covalent bonds . In 2005, Yaghi and co‐workers, for the first time, synthesized two pure two‐dimensional (2D) organic frameworks, named COF‐1 and COF‐5 .…”
Section: Introductionmentioning
confidence: 99%